The Value of Offshore Secrets: Evidence from the Panama Papers - O’Donovan, James; Wagner, Hannes F; Zeume, Stefan (Review of Financial Studies, 2019)
Abstract We exploit one of the largest data leaks, to date, to study whether and how firms use secret offshore vehicles. From the leaked data, we identify 338 listed firms as users of secret offshore vehicles and document that these vehicles are used to finance corruption, avoid taxes, and expropriate shareholders. Overall, the leak erased $$$174 billion in market capitalization among implicated firms. Following the increased transparency brought about by the leak, implicated firms experience lower sales from perceptively corrupt countries and avoid less tax. We conservatively estimate that 1 in 7 firms have offshore secrets. Received May 29, 2017; editorial decision December 2, 2018 by Editor Itay Goldstein. Authors have furnished an Internet Appendix, which is available on the Oxford University Press Web site next to the link to the final published paper online.